Itinerário diagnóstico e terapêutico das famílias e dos pacientes com doenças órfãs - Renata de Macedo Moura (2013)
Rare diseases, also known as orphan diseases, are a category of diseases that most often are chronic degenerative, debilitating and life-risk. Most have a genetic origin, are often disabling, have a lower life expectancy, affect the physical and mental skills and harm the ability to learn and work. The inborn errors of metabolism represent a heterogeneous category of genetic diseases caused by enzyme deficiencies. It is an important group of diseases that are individually rare but collectively numerous. Most of them manifest in children and represent significant cause of morbidity and mortality. For a treatable disease, the main objective of therapeutic intervention is early recognition followed by prompt treatment, which can prevent progressive neurological damage, morbidity and mortality. In Brazil, as in most parts of the world, the first challenge for patients and families is to reach a conclusive diagnosis. The difficulties are many, among them is the fact that most rare diseases are not included in newborn screening systems, what hinders access to specialized services, early diagnosis and treatment. After establishment of diagnosis, treatment - when possible - becomes the new challenge, since the Brazilian public health system called Sistema Unico de Saude (SUS) does not have a specific policy for nutritional and pharmaceutical care embracing most rare diseases. On the structure of the text, we opted for presenting the final work in the form of two items: I) Public health policies for rare diseases: examples and challenges in Asia, the Americas and Europe as a review article on the development of public health policies in Japan, EU countries, USA and Brazil. The particularities about the care services and health systems provided to patients with rare diseases in these countries were discussed, in order to identify the main problems and solutions found for the formulation of public policies. II) Diagnostic and Therapeutic Itinerary of Families and Patients with Orphans Diseases. In this one the results and analysis of interviews with mothers of patients with rare diseases are presented. The main aim of this research was to understand the trajectory of the parents and families of children with rare diseases to search for diagnosis and treatment. Specific objectives were to understand the trodden path by children with rare diseases and their families, analyze it according to the theory of Hannah Arendt and discuss the issues regarding to access to health services from the perspective of law and citizenship. The methodological approach chosen for this research was qualitative analysis, using as a data collection technique for open interviews following the method Life Story. The research was conducted with mothers of patients from the outpatient clinic for inborn errors of metabolism at Hospital das Clínicas - UFMG and at Hospital Infantil João Paulo II (FHEMIG Fundação Hospitalar do Estado de Minas Gerais). The interviews were recorded, transcribed and then analyzed using the content analysis method and hermeneutic-dialectic. The results pointed to a reality where access to specialized medical services by SUS is very difficult and the support of a multidisciplinary team needed to improve the quality of life for people with rare diseases is almost nonexistent. The families live troubles to obtain a certain diagnosis and after achieving this stage, the major barrier is to obtain treatment through medication, equipment and continuous specialized care.